2011
DOI: 10.2478/v10078-011-0045-6
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Vertical Jump Strength Metrics and 5 Meters Sprint Time

Abstract: The aim of this study was to examine the relationship between short sprint time (5 m) and strength metrics of the countermovement jump (CMJ) using a linear transducer in a group of trained athletes. Twenty-five male, trained subjects volunteered to participate in the study. Each volunteer performed 3 maximal CMJ trials on a Smith machine. Peak instantaneous power was calculated by the product of velocity taken with the linear transducer. For sprint testing, each subject performed three maximum 5 m sprints. Onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
25
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 19 publications
8
25
0
2
Order By: Relevance
“…In a study carried out by Marques et al (2011) on amateur athletes in different branches (football, futsal and handball), it was found that there was no significant relationship between 5-meter sprint times and mean propulsive velocity and peak velocity values during countermovement jumping exercise. In another study conducted by Marques et al (2009) on track and field athletes, it was stated that there was a significant correlation between short sprint performance and squat jumping.…”
Section: Discussionmentioning
confidence: 99%
“…In a study carried out by Marques et al (2011) on amateur athletes in different branches (football, futsal and handball), it was found that there was no significant relationship between 5-meter sprint times and mean propulsive velocity and peak velocity values during countermovement jumping exercise. In another study conducted by Marques et al (2009) on track and field athletes, it was stated that there was a significant correlation between short sprint performance and squat jumping.…”
Section: Discussionmentioning
confidence: 99%
“…In a study researching relationships between vertical jump strength metrics and 5 meters sprint times of amateur athletes whose events were different by Marques et al (26). it was determined that there are no considerably significant correlation between 5 meter sprint performance with MPV and PV values during countermovement jump exercise practiced by using Smith machine.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, sprint ability is a complex ability that requires proper motor coordination between joints and muscles (13). Sprint ability over very short distances (5 or 10 meters) is considered by many researchers and practitioners to require specific strength qualities and running technique, and generally is accepted that shorter sprints require a greater contribution of concentric muscle contractions and knee extensor activity (26).…”
Section: Introductionmentioning
confidence: 99%
“…5 m sprinting performance requires some other special skills such as explosiveness and techniques such as correct starting position (Duthie et al, 2006;Marques et al, 2011;Mendoza & Schöllhorn, 1993). So that, these weaker correlations might be affected by the wrong starting techniques and the difference of the explosiveness skills of the football referees.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies showed the 5, 10 and 30 meters sprint tests were related the sprint ability of the athletes (Duthie, Pyne, Ross, Livingstone, & Hooper, 2006;Köklü, Alemdaroğlu, Özkan, Koz, & Ersöz, 2015;Marques, Gil, Ramos, Costa, & Marinho, 2011;Miller, Herniman, Ricard, Cheatham, & Michael, 2006). And the studies showed the relation of the agility skills of the athletes and the T-Test, Arrowhead Agility Test and Illinois Agility Test (Amiri-Khorasani, Sahebozamani, Tabrizi, & Yusof, 2010;Chan, Lee, Fong, Yung, & Chan, 2011;Jalilvand et al, 2015;Miller et al, 2006;Muniroglu & Subak, 2018).…”
Section: Introductionmentioning
confidence: 99%